Analisis Pengaruh Dimensi Fraud Crowe Pentagon terhadap Kecurangan Akademik Mahasiswa Penerima Beasiswa - Luh Asih Utami; I Made Pradana Adiputra (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the effect of the crowe pentagon's fraud dimension, variable pressure, opportunity, rationalization, competence, and arrogance to the behavior of academic fraud bidikmisi scholarship recipients. This research is a type of quantitative research with 101respondents. The data is obtained from the results of questionnaires answers using Google Form service. This research sample was selected using purposive sampling technique and calculated by Slovin formula. Primary data in the form of respondents' answers are processed using spss version 21. The results achieved that pressure, opportunity, rationalization, competence, and arrogance had a positive and significant effect on the academic fraud behavior of scholarship recipients.